1987
DOI: 10.1111/j.1600-0404.1987.tb03546.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep movements and associated autonomic nervous activities in patients with Parkinson's disease

Abstract: Nine parkinsonian patients were studied during one night using the static charge sensitive bed (SCSB) method for the monitoring of respiration, ballistocardiogram (BCG) and body movements. The parkinsonian sleep was more restless than that of the controls. As the SCSB-defined levels of autonomic nervous activity were concerned, the amount of motor active wakefulness (MAW) was significantly (P less than 0.05) increased in parkinsonian patients, who also had less quiet sleep (P less than 0.05) than the controls.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
1

Year Published

1992
1992
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 7 publications
2
23
0
1
Order By: Relevance
“…This may be interpreted as a reduced sleep state stability of cabergoline and is in line with increased spontaneous awakenings despite greatly reduced PLM in patients with restless legs syndrome undergoing treatment with the dopamine agonist pergolide (Wetter et al, 1999). As nocturnal akinesia is a major problem in patients with PD (Laihinen et al, 1987), an increase in movement time as measured in this study may indicate a treatment-induced restoration of nocturnal mobility. The increase of movement time could therefore be related to sleep improvement despite increased sleep fragmentation.…”
Section: Discussionmentioning
confidence: 64%
“…This may be interpreted as a reduced sleep state stability of cabergoline and is in line with increased spontaneous awakenings despite greatly reduced PLM in patients with restless legs syndrome undergoing treatment with the dopamine agonist pergolide (Wetter et al, 1999). As nocturnal akinesia is a major problem in patients with PD (Laihinen et al, 1987), an increase in movement time as measured in this study may indicate a treatment-induced restoration of nocturnal mobility. The increase of movement time could therefore be related to sleep improvement despite increased sleep fragmentation.…”
Section: Discussionmentioning
confidence: 64%
“…The number of awakenings was similar to controls, while other studies [4,28] found more in PD patients. However, in these studies the patients were often receiving /-dopa.…”
Section: Discussionmentioning
confidence: 67%
“…These studies have revealed disturbed HR reactions to sleep movements in PD patients both during non-REM and REM sleep, reflecting combined sympathetic and parasympathetic defects in the cardiovascular regulation [9,16,17,21].Additionally, there is one HR variability study, carried out with a small number of more advanced PD patients on antiparkinsonian medication, that has reported night-time vagal cardiovascular dysfunction [23]. In the present study, the suppression of the HR variability was most pronounced at night, the SD 1 Poincaré component, and the LF and HF spectral components of HR variability differing significantly between the patients and the controls, reflecting dysfunction of the parasympathetic system even in untreated PD patients.…”
Section: Discussionmentioning
confidence: 99%